The Investigation of Risk-Taking Behavior in Adolescents in Terms of Attachment Styles and Social Problem-Solving - YILMAZ, Melike; TRAŞ, Zeliha (Asian Journal of Education and Training, 2019)
The aim of this study is to examine the risk-taking behavior of adolescents in terms of attachment styles and social problem-solving. The study group consists of 637 students from 9th, 10th and 11th grade, as 276 female (43.2%) and 361 male (56.7%). In order to collect data in the study, the Delinquent Behavior Scale, the Relationship Scale, the Social Problem-Solving Scale and Personal Information Form are used. Pearson Product-Moment Correlation Technique and multidimensional hierarchical regression analysis are used to analyze the data. A positive correlation is found between delinquent behaviors of adolescents and preoccupied style, which is a sub-dimension of attachment styles. While there is a positive and significant relationship between adolescents’ delinquent behaviors and negative problem orientation, which is a sub-dimension of social problem-solving, impulsive/careless style and avoidance style; there is a significant negative correlation between delinquent behaviors and rational problem-solving sub-dimension. Research results reveal that preoccupied style, rational problem-solving and avoidance style sub-dimensions are predictors of risk-taking behaviors.